The association between TNF-receptors (TNFR1 and TNFR2) and mortality as well as kidney function decline in patients with chronic kidney disease - Per Wändell; Tobias Feldreich; Anders Larsson; Philip A. Kalra; Johan Ärnlöv; Toralph Ruge; Axel C. Carlsson (Upsala Journal of Medical Sciences, 2024)
Background: Higher circulating levels of tumor necrosis factor (TNF) alpha receptors 1 (TNFR1) and 2 (TNFR2) are associated with increased long-term mortality and impaired kidney function. Aim: To study associations between levels of TNFR1 and TNFR2 and all-cause mortality as well as estimated glomerular filtration rate (eGFR) decline. Population and methods: Patients with chronic kidney disease (CKD) stages 3–5 in the Salford Kidney Study were included. Associations between one standard deviation increase in plasma TNFR1 and TNFR2 and mortality were estimated by Cox regression models with hazard ratios (HRs) and 95% confidence intervals adjusted for age, sex, eGFR based on creatinine and cystatin C, urine-protein, C-reactive protin, cardiovascular comorbidity, smoking habits, and diabetes. Differences in eGFR decline in relation to plasma TNFR1 and TNFR2 were estimated by both linear and logistic regression models, with regression coefficients and odds ratios (ORs). Results: Univariate models showed significant associations between TNFR1 (n = 985) and TNFR2 (n = 988) and all-cause mortality based on 7424 person-years at risk, but in the fully adjusted models with continuous variables significant only for TNFR2 HR 1.17 (1.03–1.34), but with a borderline value for TNFR1 HR 1.15 (1.00–1.31). For rapid decliners, that is, eGFR decline in highest TNFR-receptor quartile versus quartiles 1–3, the decline was 1.60% per month (interval 0.78–10.99). For eGFR decline in continuous models, the fully adjusted ORs were for TNFR1 1.29 (0.92–1.81) and for TNFR2 1.33 (0.90–1.98). Conclusions: TNFR2 was associated with mortality, but TNFR1 was not, although showing a borderline value. Neither TNFR1 nor TNFR2 predicted decline in kidney function. TNFR1 and TNFR2 portray interesting aspects in patients with CKD, but the clinical utility seems limited.